Surface protective film and optical member
Patent Information
- Application Number
- CN202210818145.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2022-07-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-07-12
AI Technical Summary
[0024]在上述专利文献1记载的技术中,将表面保护膜从作为被粘物的光学用膜剥离时,存在剥离静电压难以下降的问题
[0045] One aspect of the present invention provides a surface protective film that is widely applicable to the adhered objects, causes very little contamination to the adhered objects, and suppresses low peeling static voltage when the surface protective film is peeled off the adhered objects.
Smart Images

Figure CN115612421B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to surface protective films and optical components. Background Technology
[0002] When manufacturing and shipping optical films such as polarizing plates, retardation plates, lens films for displays, anti-reflection films, hard coatings, and transparent conductive films for touch panels, as well as optical products such as displays using these optical films, a surface protective film is applied to the surface of the optical film to prevent contamination or damage to the surface in subsequent processes. Regarding the visual inspection of optical films as finished products, to improve work efficiency by eliminating the need to peel off and reapply the surface protective film, visual inspection is sometimes performed directly with the surface protective film applied to the optical film.
[0003] In the manufacturing process of optical products, a surface protective film with an adhesive layer is typically applied to one side of the substrate film to prevent damage and contamination of the optical product surface. The surface protective film adheres to the optical film using the adhesive layer with micro-adhesion. The adhesive layer is designed to have micro-adhesion so that it can be easily peeled off from the surface of the optical film after use, and the adhesive will not adhere to the optical film on the adhered object (preventing the formation of so-called adhesive residue).
[0004] In recent years, during the production process of liquid crystal display panels, the static voltage generated when peeling off the surface protective film attached to the optical film can damage circuit components such as driver ICs used to control the display screen of the liquid crystal display panel. Although the number of such incidents is small, the phenomenon of orientation damage to liquid crystal molecules is also occurring.
[0005] Furthermore, in order to reduce the power consumption of liquid crystal display panels, the driving voltage of liquid crystal materials tends to be lower, and consequently, the breakdown voltage of the driving IC also tends to be lower. Recently, there has been a requirement to control the peeling static voltage of the surface protective film within the range of -0.7kV to +0.7kV.
[0006] In recent years, there has been a push towards higher resolution and higher image quality in displays, and correspondingly, there has been a push towards higher functionality in optical films. For example, there are optical films that have undergone anti-reflection (AR) and low-reflection (LR) treatments on their surfaces, as well as (AGLR) optical films that have undergone both anti-glare (AG) and low-reflection (LR) treatments.
[0007] For example, after the surface protective film is peeled off from the surface of an optical film such as a polarizer, if the surface of the optical film is contaminated by the adhesive or antistatic agent used in the surface protective film, it can sometimes become an appearance defect. Even slight contamination that is not visible in conventional polarizers may be visually identified as a defect in optical films that have undergone AR, LR, or AGLR treatment.
[0008] Furthermore, some LCD panel manufacturers use the following method to evaluate the contamination of the surface protective film on the adhered object: The surface protective film, which is adhered to an optical film such as a polarizing plate, is temporarily peeled off and re-laminated while air bubbles are present. The resulting product is then heat-treated under predetermined conditions. The surface protective film is then peeled off, and the surface of the adhered object is observed. In this evaluation method, even if the surface contamination of the adhered object is minute, if there is a difference in surface contamination between the area containing air bubbles and the area of the surface protective film in contact with the adhesive, it will remain as traces of air bubbles (sometimes called air bubble stains). Therefore, this method is very stringent in evaluating the contamination of the adhered object's surface. In recent years, even with such a stringent evaluation method, a surface protective film that does not cause contamination problems on the surface of the adhered object is required.
[0009] On the other hand, for optical films that have undergone AR, LR, or AGLR treatment, fluorine and silicon compounds are frequently used in the surface treatment. The presence of fluorine or silicon compounds tends to increase the peel voltage during the removal of the surface protective film. Therefore, the surface protective film used in such optical films needs to be designed to reduce the peel voltage compared to conventional surface protective films.
[0010] In order to prevent adverse conditions caused by high peeling static voltage when peeling a surface protective film from an optical film that is an adherend, a surface protective film using an adhesive layer containing an antistatic agent is proposed to suppress the peeling static voltage.
[0011] For example, Patent Document 1 discloses a surface protective film using an adhesive formed from an alkyltrimethylammonium salt, a hydroxyl-containing acrylic polymer, and a polyisocyanate.
[0012] In addition, Patent Document 2 discloses an adhesive composition consisting of an ionic liquid and an acrylic polymer with an acid value of 1.0 or less, and adhesive sheets using the adhesive composition.
[0013] In addition, Patent Document 3 discloses an adhesive composition formed from an acrylic polymer, a polyether polyol compound, an alkali metal salt treated with an anionic adsorption compound, and a surface protective film using the adhesive composition.
[0014] In addition, Patent Document 4 discloses an adhesive composition consisting of an ionic liquid, an alkali metal salt, and a polymer with a glass transition temperature below 0°C, and a surface protective film using the adhesive composition.
[0015] Furthermore, Patent Document 5 discloses a surface protective film having an adhesive layer in which an antistatic agent and a compound containing fluorine or silicon are added externally to an acrylic adhesive.
[0016] Existing technical documents
[0017] Patent documents
[0018] Patent Document 1: Japanese Patent Application Publication No. 2005-131957
[0019] Patent Document 2: Japanese Patent Application Publication No. 2005-330464
[0020] Patent Document 3: Japanese Patent Application Publication No. 2005-314476
[0021] Patent Document 4: Japanese Patent Application Publication No. 2006-152235
[0022] Patent Document 5: Japanese Patent Application Publication No. 2011-063712 Summary of the Invention
[0023] Technical issues
[0024] In the technology described in Patent Document 1, there is a problem that the peeling static voltage is difficult to reduce when peeling the surface protective film from the optical film, which is the adhered object. In particular, for polarizing plates that use acrylic films or PET (Polyethylene Glycol Terephthalate) films, which are non-hygroscopic, as the protective material for polarizers, there is a problem that the peeling static voltage is high when peeling the surface protective film. In the technologies described in Patent Documents 2 to 4, which use ionic liquids or alkali metal salts, which are less affected by humidity, as antistatic agents, the peeling static voltage can be reduced when peeling the surface protective film for polarizing plates that use acrylic films or PET films for polarizer protection, compared with the technology described in Patent Document 1. However, even so, for optical films that have undergone AR, LR, or AGLR treatment, the peeling static voltage may still not meet the required quality.
[0025] Patent Document 5 describes a surface protective film that has a functional layer formed by imparting functionality to the surface using fluorine-containing or silicon-containing compounds, and can reduce the peel electrostatic voltage for adhered materials such as hard-coated (HC) polarizers, AR films, and AGLR polarizers. However, with this surface protective film, since the components used as the substrate for the polarizer have changed from hygroscopic TAC films to non-hygroscopic acrylic or PET films, they become more prone to charging, and the peel electrostatic voltage when peeling off the surface protective film no longer meets the required quality. To reduce the peel electrostatic voltage, it is necessary to increase the amount of fluorine- or silicon-containing compounds added to the externally added structure. With the increase of the amount added, the surface of the optical film used as the adhered material may be contaminated. In particular, for optical films treated with AR, LR, or AGLR, contamination is easily observed, and even trace amounts of residual contaminants may reduce the appearance quality of the optical film.
[0026] Thus, optical films treated with AR, LR, or AGLR tend to have higher peel static voltage when the surface protective film is peeled off, and even trace amounts of contamination can become appearance defects. Therefore, there is a need for a surface protective film for optical films that can also be used for optical films treated with AR, LR, or AGLR, causes very little contamination to the adhered object, and suppresses a low peel static voltage when the surface protective film is peeled off from the adhered object.
[0027] One aspect of the present invention is made in view of the above circumstances, and its objective is to provide a surface protective film and optical components that have a wide range of applications for the adherends, cause less contamination to the adherends, and suppress the peeling static voltage.
[0028] Technical solution
[0029] The inventors have conducted in-depth research on this topic.
[0030] A surface protective film was studied that causes less contamination to the adhered object and also reduces the peeling static voltage when peeling the surface protective film from the adhered object for optical films that have undergone AR, LR, or AGLR treatment, especially for polarizing plates that use acrylic films or PET films with low hygroscopicity and easy charging.
[0031] In this study, the phenomenon of peel charging that occurs when the surface protective film is peeled off from the optical film used as the adherend was considered. Peel charging is the phenomenon of charging that occurs when two materials are separated from a contact state (peeled off), and it is believed that the more the two materials are separated along the charged sequence, the greater the charge.
[0032] In optical films that have undergone anti-reflection (AR) or low-reflection (LR) treatments on their surfaces, materials with low refractive index, such as fluorine, are used on the surface to exhibit anti-reflection and low-reflection functions.
[0033] When considering the phenomenon of peeling the surface protective film from the optical film that is the adhered object, the peeling of the surface protective film can be considered as a change from a state of contact between the surface of the optical film and the adhesive layer of the surface protective film to a separation at the interface between the surface of the optical film and the adhesive layer.
[0034] The inventors believe that if the charge sequence of the material on the surface of the optical film is close to that of the material in the adhesive layer, the peel voltage will be reduced. Therefore, fluorine is often used as a low-refractive-index material in anti-reflective and low-reflective treatments, and it is believed that using fluorine-based materials in the adhesive layer may reduce the peel voltage.
[0035] On the other hand, even if the charge (electromotive force) generated during peeling is small, the charge will remain if the static electricity carried on the surface is not released quickly. Therefore, it is believed that it is necessary to release the static electricity quickly. Thus, it was found that siloxane surfactants are effective for this purpose, thereby completing the present invention.
[0036] One design concept of this invention is to reduce the electromotive force generated during peeling by adding fluorinated surfactants, and to reduce the peeling static voltage by adding siloxane surfactants, thereby instantaneously releasing the carried static electricity.
[0037] To address the aforementioned problems, one aspect of the present invention involves adding fluorinated surfactants to the adhesive layer to reduce the electromotive force generated during peeling, and adding siloxane surfactants to instantly release the static electricity carried by the peeling, thereby reducing the peeling static voltage.
[0038] One aspect of the present invention provides a surface protective film comprising: a substrate film made of a transparent resin; an adhesive layer formed on one side of the substrate film; and a release film formed on the side of the adhesive layer opposite to the substrate film. The release film comprises: a resin film; and a release agent layer laminated on the side of the resin film on the side of the adhesive layer. The release agent layer contains a release agent mainly composed of dimethylpolysiloxane and an antistatic agent. The adhesive layer is formed of an adhesive containing a (meth)acrylate copolymer, a siloxane surfactant, a fluorinated surfactant, and a crosslinking agent. The crosslinking agent crosslinks the (meth)acrylate copolymer. The ratio of the siloxane surfactant to the fluorinated surfactant in the adhesive (siloxane surfactant / fluorinated surfactant) is a mass ratio of 20 / 80 to 90 / 10 based on solid components.
[0039] The above-mentioned (meth)acrylate copolymer is preferably a copolymer containing one or more of the following: acrylates having alkyl groups, acrylates having alkylene oxide groups, and acrylates having hydroxyl groups.
[0040] The antistatic agent mentioned above is preferably an ionic compound.
[0041] The antistatic agent is preferably an alkali metal salt or an ionic compound that is solid at 20°C.
[0042] Preferably, the surface protective film has a low-speed adhesive force of 0.2 N / 25 mm or less when peeling at a peeling speed of 0.3 m / min relative to the low-reflection polarizing plate (LR polarizing plate), a high-speed adhesive force of 0.8 N / 25 mm or less when peeling at a peeling speed of 30 m / min, and a peeling static voltage of -0.7 kV to +0.7 kV or less during peeling.
[0043] Another aspect of the present invention provides an optical component having the aforementioned surface protective film adhered to it.
[0044] Invention Effects
[0045] One aspect of the present invention provides a surface protective film that is widely applicable to the adhered objects, causes very little contamination to the adhered objects, and suppresses low peeling static voltage when the surface protective film is peeled off the adhered objects.
[0046] According to one aspect of the present invention, the surface of the optical film can be protected, and large peeling static voltage can be suppressed when peeling off the surface protective film, and contamination of the adhered material can be suppressed, thereby achieving increased productivity and yield. Attached Figure Description
[0047] Figure 1This is a cross-sectional view illustrating the concept of a surface protective film in an embodiment.
[0048] Figure 2 This is a cross-sectional view showing the state where the release film has been peeled off from the surface protective film of the embodiment.
[0049] Figure 3 This is a cross-sectional view illustrating one embodiment of the optical component of the present invention.
[0050] Symbol Explanation
[0051] 1…substrate film, 2…adhesive layer, 3…resin film, 4…release agent layer, 5…release film, 6…release agent, 7…antistatic agent, 8…adhered object (optical component), 10…surface protective film, 11…surface protective film with release film removed, 20…optical component with surface protective film attached. Detailed Implementation
[0052] The present invention will now be described in detail based on its embodiments.
[0053] Figure 1 This is a cross-sectional view illustrating the concept of a surface protective film in an embodiment.
[0054] like Figure 1 As shown, in this embodiment, the surface protective film 10 is on one surface of the transparent substrate film 1 ( Figure 1 An adhesive layer 2 is formed on the upper surface of the resin film 3. A release film 5, on which a release agent layer 4 is formed on the surface of the resin film 3, is adhered to the surface of the adhesive layer 2. In other words, the surface protective film 10 is composed of a substrate film 1, an adhesive layer 2, and a release film 5 stacked sequentially. The release film 5 is composed of a resin film 3 and a release agent layer 4 stacked together.
[0055] [Substrate Film]
[0056] As the substrate film 1, a substrate film made of a transparent and flexible resin is used. This allows for visual inspection of the optical component while the surface protective film 10 is adhered to the optical component as the adhered object. The transparent resin film used as the substrate film 1 is preferably a polyester film such as polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, or polybutylene terephthalate. Besides polyester films, films made of other resins may also be used, provided they possess the necessary strength and optical adaptability. The substrate film 1 can be an unstretched film or a film formed by uniaxial or biaxial stretching. Furthermore, the stretch ratio of the stretched film and the orientation angle in the axial direction formed during the crystallization of the stretched film can be controlled to specific values.
[0057] "Transparency" means, for example, that when measured in the wavelength range of 380 nm to 780 nm, the visible light transmittance, calculated as the average transmittance in the thickness direction across the entire wavelength range, is 50% or more (preferably 70% or more, more preferably 80% or more). The light transmittance can be measured according to the method for "Calculation of Total Light Transmittance and Total Light Reflectance in Plastics" as specified in JIS K7375:2008.
[0058] The thickness of the substrate film 1 is not particularly limited. For example, a thickness of about 12 to 100 μm is preferred. A thickness of about 20 to 50 μm is easier to process and is more preferred.
[0059] Additionally, as needed, the adhesive layer 2 can be formed on the opposite side of the substrate film 1 (where the adhesive layer 2 is formed). Figure 1 The lower surface (middle section) is provided with an anti-fouling layer to prevent surface contamination, an antistatic layer, and a hard coating to prevent damage. Additionally, the surface of the substrate film 1 can be treated with surface modification based on corona discharge, or with the application of an anchoring coating agent for improved adhesion.
[0060] [Adhesive layer]
[0061] Adhesive layer 2 is an adhesive layer that adheres to the surface of the adhered object, can be easily peeled off after use, and does not easily contaminate the adhered object. Adhesive layer 2 is formed of an adhesive containing a (meth)acrylate copolymer, a siloxane surfactant, a fluorinated surfactant, and a crosslinking agent. Adhesive layer 2 is an adhesive layer formed by crosslinking the (meth)acrylate copolymer using the aforementioned crosslinking agent. Adhesive layer 2 is transparent.
[0062] Examples of (meth)acrylate copolymers include copolymers obtained by copolymerizing (1) alkyl (meth)acrylates, (2) olefinic (meth)acrylates, and (3) hydroxyl (meth)acrylates. A (meth)acrylate copolymer may be a copolymer containing one or more of (1), (2), and (3).
[0063] Examples of alkyl-containing (meth)acrylates include: methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, etc. Undecyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, octadecyl methacrylate, myristyl methacrylate, isomyristyl methacrylate, cetyl methacrylate, isocetyl methacrylate, stearyl methacrylate, isostearyl methacrylate, etc.
[0064] A (meth)acrylate containing an olefinic group is any compound in which one of the multiple hydroxyl groups of a polyalkylene glycol is esterified to form a (meth)acrylate. Because the (meth)acrylate group becomes a polymerizable group, a (meth)acrylate containing an olefinic group can copolymerize with the main polymer. Other hydroxyl groups can remain OH, or can be alkyl ethers such as methyl ethers or ethyl ethers, or saturated carboxylic acid esters such as acetates. Examples of alkylene groups in polyalkylene glycols include ethylene, propyleneene, and butylene, but these are not limited to. Polyalkylene glycols can be copolymers of two or more of the following: polyethylene glycol, polypropylene glycol, and polybutane glycol.
[0065] Examples of copolymers of polyalkylene glycols include polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, and polyethylene glycol-polypropylene glycol-polybutylene glycol. These copolymers can be block copolymers or random copolymers. The average number of repeating olefin oxygen atoms constituting the polyalkylene glycol chain is preferably 3 to 14. "The average number of repeating olefin oxygen atoms" refers to the average number of repeating olefin oxygen units in the "polyalkylene glycol chain" portion contained in the molecular structure of the polyalkylene glycol mono(meth)acrylate monomer.
[0066] The polyalkylene glycol mono(meth)acrylate monomer is preferably selected from at least one of polyalkylene glycol mono(meth)acrylate, methoxy polyalkylene glycol (meth)acrylate, and ethoxy polyalkylene glycol (meth)acrylate.
[0067] More specifically, examples include polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polybutylene glycol mono(meth)acrylate, polyethylene glycol-polypropylene glycol-mono(meth)acrylate, polyethylene glycol-polybutylene glycol-mono(meth)acrylate, polypropylene glycol-polybutylene glycol-mono(meth)acrylate, polyethylene glycol-polypropylene glycol-polybutylene glycol-mono(meth)acrylate; methoxy polyethylene glycol-(meth)acrylate, methoxy polypropylene glycol-(meth)acrylate, methoxy polybutylene glycol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, methoxy- Polyethylene glycol-polybutanediol-(meth)acrylate, methoxy-polypropylene glycol-polybutanediol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-polybutanediol-(meth)acrylate; ethoxy-polyethylene glycol-(meth)acrylate, ethoxy-polypropylene glycol-(meth)acrylate, ethoxy-polybutanediol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutanediol-(meth)acrylate, ethoxy-polypropylene glycol-polybutanediol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-polybutanediol-(meth)acrylate, etc.
[0068] Examples of hydroxyl-containing (meth)acrylates include hydroxyalkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; and hydroxyl-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0069] (Meth)acrylate copolymers can be copolymers comprising one or more of (4) carboxyl (meth)acrylates, (5) carboxyl (meth)acrylic acid, and (6) nitrogen-containing vinyl monomers.
[0070] Examples of acrylates containing carboxyl groups include carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxylated polycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0071] Examples of nitrogen-containing vinyl monomers include vinyl monomers containing amide bonds, vinyl monomers containing amino groups, and vinyl monomers with nitrogen-containing heterocyclic structures. More specifically, examples include cyclic nitrogen-containing vinyl compounds with N-vinyl-substituted heterocyclic structures such as N-vinyl-2-pyrrolidone, N-vinylpyrrolidone, methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidinone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazolium, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-vinyllauronactam; and N-(meth)acryloylmorpholine, N-(meth)acryloylpiperazine, N-(meth)acryloylaziridine, and N- (Methacryloylaziridine), N-(methacryloylpyrrolidine), N-(methacryloylpiperidine), N-(methacryloylaziridine-heptane, N-(methacryloylaziridine-octane, etc.) are cyclic nitrogen-vinyl compounds with heterocyclic structures substituted with N-(methacryloyl) groups; N-cyclohexylmaleimide, N-phenylmaleimide, and other cyclic nitrogen-vinyl compounds with heterocyclic structures containing nitrogen atoms and alkene unsaturated bonds within the ring; (meth)acrylamide, N-methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, etc. Unsubstituted or monoalkyl-substituted (meth)acrylamides such as methacrylamide; dialkyl-substituted (meth)acrylamides such as N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropylacrylamide, N,N-diisopropyl (meth)acrylamide, N,N-dibutyl (meth)acrylamide, N-ethyl-N-methyl (meth)acrylamide, N-methyl-N-propyl (meth)acrylamide, and N-methyl-N-isopropyl (meth)acrylamide; methyl N,N-dimethylamino (meth)acrylate, N,N-dimethylamino (meth)acrylamide, etc. Dialkylamino(meth)acrylates, including ethyl acetate, propyl N,N-dimethylamino(meth)acrylate, isopropyl N,N-dimethylamino(meth)acrylate, butyl N,N-dimethylamino(meth)acrylate, methyl N,N-diethylamino(meth)acrylate, ethyl N,N-diethylamino(meth)acrylate, ethyl N-ethyl-N-methylamino(meth)acrylate, ethyl N-methyl-N-propylamino(meth)acrylate, ethyl N-methyl-N-isopropylamino(meth)acrylate, ethyl N,N-dibutylamino(meth)acrylate, and ethyl tert-butylamino(meth)acrylate;N,N-Dimethylaminopropyl (meth)acrylamide, N,N-Diethylaminopropyl (meth)acrylamide, N,N-Dipropylaminopropyl (meth)acrylamide, N,N-Diisopropylaminopropyl (meth)acrylamide, N-Ethyl-N-methylaminopropyl (meth)acrylamide, N-Methyl-N-propylaminopropyl (meth)acrylamide, N-Methyl-N-isopropylaminopropyl (meth)acrylamide, and other N,N-dialkyl-substituted aminopropyl (meth)acrylamides; N-vinylformamide, N-vinylacetamide, N-vinyl-N-methylacetamide, and other N-vinylcarboxylic acid amides; N-methoxymethyl (meth)acrylamide, N-ethoxyethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone acrylamide, N,N-methylenebis(meth)acrylamide, and other (meth)acrylamides; (meth)acrylonitrile and other unsaturated carboxylic acid nitriles; etc.
[0072] As described above, adhesive layer 2 contains siloxane surfactants.
[0073] Siloxane surfactants are added to improve conductivity and quickly release static electricity generated during the peeling of the protective film on the surface, thereby reducing the charge.
[0074] Reference Example 1 below is a test result confirming that the conductivity of the adhesive layer is improved by adding a siloxane surfactant.
[0075] [Reference Example 1]
[0076] Adhesive layers were prepared by adding a siloxane surfactant to an adhesive composition consisting of a (meth)acrylate copolymer, an antistatic agent, and a crosslinking agent, and adhesive layers were prepared without adding a siloxane surfactant to the aforementioned adhesive composition. The surface resistivity of the obtained adhesive layers was measured using a high resistance meter (Hirestar UP, manufactured by Mitsubishi Chemical Corporation, Japan).
[0077] (Preparation of the adhesive layer)
[0078] An adhesive was prepared consisting of a copolymer of 80 parts by weight of 2-ethylhexyl acrylate, 17 parts by weight of methoxy polyethylene glycol (400) methacrylate, and 3 parts by weight of 2-hydroxyethyl acrylate. The adhesive composition was prepared by stirring and mixing the mixture with 0.3 parts by weight of lithium bis(trifluoromethanesulfonyl)imide as an antistatic agent and 2 parts by weight of Coronate HX (manufactured by Tosoh Corporation, a registered trademark) as a crosslinking agent in a 40% ethyl acetate solution of 100 parts by weight of the adhesive.
[0079] Using an applicator, the prepared adhesive composition was applied to the surface of a 38 μm thick polyethylene terephthalate (PET) film with a dried adhesive layer thickness of 20 μm. This adhesive layer was then heated and dried in a hot air circulating oven at 100°C for 3 minutes to obtain an adhesive film. This adhesive film was constructed by forming an adhesive layer on one side of the PET film. A release film (DIAFOIL MRF25, Mitsubishi Chemical, registered trademark; a film treated with a 25 μm thick PET film using a siloxane release agent) was then laminated onto the surface of the adhesive layer. The resulting adhesive sheet was cured at 40°C for 3 days. This adhesive sheet is referred to as "adhesive sheet without added siloxane surfactant".
[0080] The release film was peeled off from the adhesive sheet without any added siloxane surfactant, and the surface resistance of the adhesive layer was measured using a high resistance meter under measurement conditions of 100V and 30 seconds.
[0081] Except for adding 0.1 parts by weight of the siloxane surfactant DowSil L-7002 (manufactured by Dow Toray Industries, Inc., a registered trademark) to the adhesive composition described above, the same operation as described above is performed to obtain the adhesive sheet. This adhesive sheet is referred to as "adhesive sheet with added siloxane surfactant".
[0082] The release film was peeled off from the adhesive sheet containing siloxane surfactants, and the surface resistance of the adhesive layer was measured using a high resistance meter under measurement conditions of 100V and 30 seconds.
[0083] The surface resistivity of the adhesive layer was measured as follows.
[0084] [Surface resistivity of the adhesive layer of the adhesive sheet]
[0085] The surface resistivity of the adhesive layer without the addition of siloxane surfactants is 5E+13Ω / □.
[0086] The surface resistivity of the adhesive layer with added siloxane surfactants is 2E+11Ω / □.
[0087] The experimental results show that adding siloxane surfactants reduces the surface resistivity of the adhesive layer. These results also indicate that adding siloxane surfactants improves the conductivity of the adhesive layer.
[0088] Siloxane surfactants are substances that contain both hydrophilic and hydrophobic groups in a single molecule, with the hydrophobic group being a polysiloxane. Examples of polysiloxanes include polydimethylsiloxane and polymethylalkylsiloxane. Polyether-modified siloxanes (e.g., polyether-modified polysiloxanes) are also examples of siloxane surfactants. Polyether-modified polysiloxanes include polyether-modified polydimethylsiloxane, polyether-modified polymethylalkylsiloxane, and polyglycol-modified polysiloxane. Examples of polyether structures for polyether-modified polysiloxanes include polyethylene glycol and polypropylene glycol structures.
[0089] Siloxane surfactants can be, for example, compounds represented by general formula (1).
[0090] R1-Si(CH3)2-[OSi(CH3)2] n -[OSi(CH3)R2] m -OSi(CH3)2-R3···(1)
[0091] R1 and R3 are alkyl groups. R2 is a compound represented by general formula (2). n and m are integers greater than or equal to 1.
[0092] -(CH2) p -(OC2H4) q -(OC3H6) r -R4 ···(2)
[0093] p is an integer from 1 to 6, q is an integer from 0 to 50, and r is an integer from 0 to 50. q+r is an integer greater than or equal to 1. R4 is a hydrogen atom or an alkyl group.
[0094] As siloxane surfactants, specific examples include KF-351A, KF-352A, KF-353, KF-354L, KF-355A, KF-642, KF-644, KF-6012, KF-6017P, KF-6020, KF-6204 (manufactured by Shin-Etsu Chemical Industry Co., Ltd.); SH3746, SH3771, SH3772, SH3773M, SH8400, and SH87. 00, SF8410, FZ-2110, FZ-2123, L-7001, L-7002 (manufactured by Toray Industries, Inc.); TSF-4440, TSF-4441, TSF-4445, TSF-4446, TSF-4450 (manufactured by Momentive Performance Materials, Inc.); BYK-300, BYK-306, BYK-307, BYK-320, BYK-325, BYK-330 (manufactured by BYK Chemical Company, Inc.), etc.
[0095] L-7002 contains the compound represented by the above general formula (1). L-7002 is a polyether-modified polydimethylsiloxane. SF8410 is a polyether-modified polydimethylsiloxane.
[0096] Apart from BYK-320 and BYK-325, the siloxane surfactants exemplified here are polyether-modified polydimethylsiloxanes. BYK-320 and BYK-325 are polyether-modified polymethylalkylsiloxanes.
[0097] The amount of siloxane surfactant added to the adhesive varies depending on the type of siloxane surfactant and its compatibility with the adhesive. It can be set by considering factors such as the desired peel voltage when the protective film 10 is peeled from the adherend, the potential for contamination of the adherend, and the adhesive properties. A higher amount of siloxane surfactant increases the likelihood of reducing the peel voltage during the removal of the protective film, but it also increases the likelihood of contaminating the adherend; therefore, an appropriate amount needs to be selected.
[0098] The amount of siloxane surfactant added can be set to 0.005 to 0.5 parts by weight (more preferably 0.01 to 0.1 parts by weight) relative to 100 parts by weight of (meth)acrylate copolymer.
[0099] As described above, adhesive layer 2 contains fluorinated surfactants.
[0100] Fluorinated surfactants are added to optical films that have undergone AR, LR, or AGLR treatment in order to make the charged sequence of the optical film surface and the adhesive layer similar and to reduce the electromotive force when the surface protective film is peeled off.
[0101] Fluorinated surfactants are surfactants whose molecules contain fluorine. Fluorinated surfactants are substances that have both hydrophilic and hydrophobic groups in a single molecule; for example, the hydrophobic group may contain fluorine.
[0102] As fluorinated surfactants, nonionic surfactants can be used, for example. Fluorinated surfactants, for example, have a perfluorinated group as a fluorinated hydrophobic group. A "perfluorinated group" is a group obtained by replacing all hydrogen atoms in a hydrocarbon (e.g., an alkyl group) with fluorine atoms.
[0103] Perfluorinated olefins can be used as fluorinated surfactants. Perfluorinated olefin adducts (perfluorinated alkyl ethylene oxide adducts) are preferred as fluorinated surfactants.
[0104] Examples of fluorinated surfactants include MEGAFAC (trademark name) manufactured by DISENG AG, FTERGENT (trademark name) manufactured by NEOMS AG, and Surflon (trademark name) manufactured by AGC Chingmei Chemical AG.
[0105] Specifically, examples of fluorinated surfactants include MEGAFAC (registered trademark) F-114, F-251, F-253, F-281, F-410, F-430, F-444, F-470, F-477, F-510~F-563, F-565, F-568~F570, F-572, F-574~F576, R-40, R-41, R-94, RS-56, RS-75, RS-78, RS-90, DS-21, etc.; and FTERGENT (registered trademark) 100, 110, 150, 300, 310, 320, 251, 208M, 212M, 215M, 25 0, 209F, 222F, 245F, 208G, 218GL, 240G, 212P, 220P, 228P, FTX-218, DFX-18, 710FL, 730FL, 610FM, 683, 601AD, 602A, 650AC, 681, etc.; Surflon (registered trademark) S-211, S-221, S-231, S-232, S-233, S-241, S-242, S-243, S-420, S-431, S-368, S-611, S-647, S-651, S-653, S-656, S-658, S-693, FPE-50, etc.
[0106] The amount of fluorinated surfactant added to the adhesive varies depending on the type of fluorinated surfactant and its compatibility with the adhesive. It should be set considering factors such as the desired peel voltage when the protective film 10 is peeled from the adherend, the potential for contamination of the adherend, and the adhesive properties. A higher amount of fluorinated surfactant increases the likelihood of reducing the peel voltage when peeling the protective film; however, because it easily contaminates the adherend, an appropriate amount needs to be selected.
[0107] The amount of fluorinated surfactant added can be set to, for example, 0.005 to 0.5 parts by weight (more preferably 0.01 to 0.1 parts by weight) relative to 100 parts by weight of (meth)acrylate copolymer.
[0108] It is important that the surface protective film 10 is made in combination with fluorinated and siloxane surfactants. The surface protective film of the embodiment, by using both fluorinated and siloxane surfactants, can reduce the peel electrostatic voltage during peeling, even with small amounts added. By reducing the amount of surfactant added, it is less likely to contaminate the adhered material, thus simultaneously achieving the opposite characteristics of adhering material contamination and reduced peel electrostatic voltage.
[0109] The ratio of siloxane surfactants to fluorinated surfactants in adhesives (siloxane surfactant / fluorinated surfactant) is a mass ratio of 20 / 80 to 90 / 10 based on solid components. The ratio of siloxane surfactants to fluorinated surfactants is the mass ratio (N1 / N2) of the amount of siloxane surfactant added (N1) to the amount of fluorinated surfactant added (N2).
[0110] If the ratio of siloxane surfactant to fluorinated surfactant is less than 20 / 80 (i.e., if there is little siloxane surfactant), the rate of charge release during the peeling of the protective film 10 is slower, resulting in a higher peel electrostatic voltage. Even if the amount of surfactant added is increased when the ratio of siloxane surfactant to fluorinated surfactant is less than 20 / 80, the peel electrostatic voltage during the peeling of the protective film can be reduced, but this is not preferred due to increased contamination of the adhered material and resulting appearance defects.
[0111] On the other hand, if the ratio of siloxane surfactants to fluorinated surfactants is higher than 90 / 10 (that is, if there is more siloxane surfactant), the electromotive force generated when peeling off the surface protective film 10 increases, resulting in a higher peel electrostatic voltage. Even when the ratio of siloxane surfactants to fluorinated surfactants is higher than 90 / 10, increasing the amount of surfactant added can reduce the peel electrostatic voltage when peeling off the surface protective film, but this is not preferable because it increases contamination of the adhered material and causes appearance defects.
[0112] As described above, adhesive layer 2 is an adhesive layer formed by crosslinking (meth)acrylate copolymer, and the adhesive layer contains a crosslinking agent.
[0113] A crosslinking agent is used for the purpose of crosslinking (meth)acrylate copolymers. Examples of crosslinking agents include isocyanate compounds, epoxy compounds, melamine compounds, and metal chelating compounds. Among these, isocyanate compounds are preferred.
[0114] The isocyanate compound can be a difunctional or higher isocyanate compound. A difunctional or higher isocyanate compound can be selected from one or more polyisocyanate compounds having at least two isocyanate (NCO) groups in one molecule. Polyisocyanate compounds are classified into aliphatic isocyanates, aromatic isocyanates, acyclic isocyanates, and cycloaliphatic isocyanates, and the present invention can be any of these. Specific examples of polyisocyanate compounds include aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and trimethylhexamethylene diisocyanate (TMDI), and aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), phenylenediamine diisocyanate (XDI), hydrogenated phenylenediamine diisocyanate (H6XDI), dimethyl diphenylene diisocyanate (TOID), and toluene diisocyanate (TDI).
[0115] Examples of trifunctional or higher isocyanate compounds include biuret-modified forms and isocyanurate-modified forms of difunctional isocyanate compounds (compounds having two NCO groups per molecule). Trifunctional or higher isocyanate compounds can also be adducts (polyol-modified forms) of difunctional isocyanate compounds and trivalent or higher polyols (compounds having at least three OH groups per molecule). Examples of trivalent or higher polyols include trimethylolpropane (TMP) and glycerol.
[0116] Difunctional isocyanate compounds and trifunctional isocyanate compounds can be used alone, or they can be used in combination.
[0117] There is no particular limit to the amount of crosslinking agent to be added. The amount to be added should be determined based on the required adhesive properties such as the amount of functional groups (hydroxyl content) and adhesive strength of the (meth)acrylate copolymer.
[0118] The amount of crosslinking agent added can be, for example, 0.1 to 10 parts by weight (more preferably 0.5 to 5 parts by weight) for 100 parts by weight of (meth)acrylate copolymer.
[0119] Depending on the requirements, tackifiers such as rosin, coumarone-indene, terpenes, petroleum compounds, and phenols can be added to adhesive layer 2. Curing accelerators that promote the crosslinking reaction between the (meth)acrylate copolymer and the crosslinking agent can also be added. When a polyisocyanate compound is used as the crosslinking agent, the crosslinking accelerator only needs to be a substance that functions as a catalyst for the reaction (crosslinking reaction) between the copolymer and the crosslinking agent. Examples of crosslinking accelerators include amine compounds such as tertiary amines. Crosslinking accelerators can also be organometallic compounds such as metal chelating compounds, organotin compounds, organolead compounds, and organozinc compounds. Furthermore, to suppress excessive viscosity increase and gelation of the adhesive composition after the addition of the crosslinking agent and to extend the pot life of the adhesive composition, curing inhibitors such as ketene-enol tautomers can be added to adhesive layer 2 as needed.
[0120] The thickness of the adhesive layer 2 is not particularly limited, but is preferably about 5 to 40 μm, more preferably about 10 to 30 μm. Furthermore, the adhesive force (low-speed adhesive force) at a peel speed of 0.3 m / min to the surface of the adherend is preferably 0.3 N / 25 mm or less, more preferably 0.2 N / 25 mm or less. Additionally, the adhesive force (high-speed adhesive force) at a peel speed of 30 m / min is preferably 0.8 N / 25 mm or less. If the high-speed adhesive force exceeds 0.8 N / 25 mm, the workability when peeling off the surface protective film after use may deteriorate. The adhesive force of the adhesive layer 2 can be adjusted by the amount of crosslinking agent (curing agent), siloxane surfactant, or fluorinated surfactant added.
[0121] [Release film]
[0122] The release film 5 is formed by laminating a release agent layer 4 on one side of the resin film 3. The release agent layer 4 is laminated on the side of the adhesive layer 2 of the resin film 3. Figure 1 (the lower surface of the middle).
[0123] Examples of resin films 3 include polyester films, polyamide films, polyethylene films, polypropylene films, and polyimide films. Polyester films are particularly preferred as resin films 3 due to their excellent transparency and relatively low cost. The resin film 3 can be a non-stretched film or a film formed by uniaxial or biaxial stretching. Furthermore, the stretch ratio of the stretched film and the orientation angle in the axial direction formed during the crystallization of the stretched film can be controlled to specific values.
[0124] The thickness of the resin film 3 is not particularly limited, but for example, a thickness of about 12 to 100 μm is preferred. If the thickness is about 20 to 50 μm, it is easier to process, which is even more preferred.
[0125] In addition, as needed, the surface of the resin film 3 can also be subjected to surface modification based on corona discharge, coating with anchoring agents, and other easy-to-adhere treatments.
[0126] The release agent layer 4 contains a release agent and an antistatic agent with dimethylpolysiloxane as the main component.
[0127] Examples of release agents include known siloxane-based release agents such as addition reaction type, condensation reaction type, cationic polymerization type, and free radical polymerization type. Commercially available products as addition reaction type siloxane release agents include, for example, KS-776A, KS-847T, KS-779H, KS-837, KS-778, KS-830 (manufactured by Shin-Etsu Chemical Co., Ltd.), SRX-211, SRX-345, SRX-357, SD7333, SD7220, SD7223, LTC-300B, LTC-350G, and LTC-310 (manufactured by Dow Toray Industries, Inc.). Commercially available products as condensation reaction type release agents include, for example, SRX-290 and SYLOFF-23 (manufactured by Dow Toray Industries, Inc.). Examples of commercially available cationic polymers include TPR-6501, TPR-6500, UV9300, VU9315, UV9430 (manufactured by Momentive Advanced Materials Co., Ltd.), and X62-7622 (manufactured by Shin-Etsu Chemical Co., Ltd.). Examples of commercially available free radical polymers include X62-7205 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0128] As an antistatic agent, it is preferable to have good dispersibility in solutions of release agents with dimethylpolysiloxane as the main component and not hinder the curing of the release agent.
[0129] exist Figure 1 The diagram shows stripping agent 6 and antistatic agent 7. Antistatic agent 7 is dispersed in stripping agent 6.
[0130] like Figure 2 As shown, antistatic agent 7 is transferred from release agent layer 4 to the surface of adhesive layer 2, imparting antistatic function to adhesive layer 2. Therefore, the antistatic agent preferably does not react with the release agent, which is mainly composed of dimethylpolysiloxane. Examples of antistatic agents that do not react with the release agent include alkali metal salts, ionic liquids that are liquid at room temperature, and ionic solids that are solid at room temperature. Ionic liquids are also called ionic liquids. Ionic liquids and ionic solids are ionic compounds.
[0131] Examples of alkali metal salts include those composed of lithium, sodium, and potassium. Specifically, for example, those composed of Li are preferred. + Na + K + One or more cations and Cl -,Br - I - BF4 - PF6 - SCN - ClO4 - CF3SO3 - (CF3SO2)2N - (C2F5SO2)2N - (CF3SO2)3C - Metal salts composed of one or more anions. Particularly preferred examples include lithium salts such as LiBr, LiI, LiBF4, LiPF6, LiSCN, LiClO4, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, and Li(CF3SO2)3C. These alkali metal salts can be used alone or in combination of two or more.
[0132] Li(CF3SO2)2N is lithium bis(trifluoromethanesulfonyl)imide.
[0133] Ionic compounds, such as ionic liquids and ionic solids, are ionic compounds that possess both cations and anions. Examples of cations include cyclic amidine ions such as imidazolium ions, pyridinium ions, ammonium ions, sulfonium ions, phosphonium ions, and tri-n-butylmethylammonium ions. Examples of anions include C... n H 2n+1 COO - C n F 2n+1 COO - NO3 - CnF 2n+1 SO3 - (C) n F 2n+1 SO2)2N - (C) n F 2n+1 SO2)3C - PO4 3- AlCl4 - Al2Cl7 - ClO4 - BF4 - PF6 - AsF6 - SbF6 - wait.
[0134] As an ionic liquid, an example is "(n—C4H9)3(CH3)N". +- N(SO2CF3)2""tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide".
[0135] The amount of antistatic agent added to the release agent varies depending on the type of antistatic agent and its affinity with the release agent. The amount of antistatic agent added only needs to be set by considering the desired peeling static voltage when peeling the surface protective film 10 from the adhered object, the contamination of the adhered object, and the adhesive properties.
[0136] The release agent layer 4 can be a mixture of the release agent and the antistatic agent. There are no particular limitations on the mixing method of the release agent and the antistatic agent. It can be any method such as (1) adding the antistatic agent to the release agent and mixing it, then adding and mixing the catalyst for curing the release agent; (2) pre-diluting the release agent with an organic solvent and then adding and mixing the antistatic agent and the catalyst for curing the release agent; and (3) pre-diluting the release agent in an organic solvent, then adding and mixing the catalyst, and then adding and mixing the antistatic agent. Adhesion enhancers such as silane coupling agents can be added to the release agent layer 4 as needed. Materials that assist in the antistatic effect, such as compounds containing polyoxyalkylene groups, can also be added to the release agent layer 4.
[0137] The mixing ratio of the release agent and the antistatic agent is not particularly limited, but it is preferably about 5 to 100 parts by weight of the antistatic agent (based on the solid component) per 100 parts by weight of the release agent. If the amount of antistatic agent added, converted from the solid component, is more than 5 parts by weight per 100 parts by weight of the release agent, the amount of antistatic agent transferred to the adhesive layer surface can be increased, thereby making it easier for the adhesive to perform its antistatic function.
[0138] When the amount of solid component of the antistatic agent added is less than 100 parts by weight relative to 100 parts by weight of the solid component of the release agent, it can prevent the release agent and antistatic agent from being transferred together to the surface of the adhesive layer. Therefore, it can prevent the reduction of the adhesive properties of the adhesive.
[0139] The thickness of the release agent layer 4 is not particularly limited, but it is mostly around 0.05 μm to 0.4 μm. When the thickness of the release agent layer 4 is greater than 0.05 μm, the peeling performance is better. Therefore, the peeling force when peeling off the release film 5 is lower, and the workability is better. When the thickness of the release agent layer 4 is less than 0.4 μm, the cost can be controlled.
[0140] The method for forming the adhesive layer 2 on the substrate film 1 and the method for attaching the release film 5 to the adhesive layer 2 can be carried out by any known method and are not particularly limited. Specifically, the following methods can be used: (1) applying a resin composition (adhesive composition) to one side of the substrate film 1 and drying it to form the adhesive layer 2, and then attaching the release film 5; (2) applying a resin composition (adhesive composition) to the surface of the release film 5 and drying it to form the adhesive layer 2, and then attaching the substrate film 1, etc.
[0141] The method for forming the adhesive layer 2 on the surface of the substrate film 1 can be a known method. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot extrusion coating, Mayer bar coating, and air knife coating can be used.
[0142] Preferably, the surface potential of the protective film 10 having the above-described configuration when peeled off from the optical film, which is the adherend, is -0.7 kV to +0.7 kV. More preferably, the surface potential is -0.5 kV to +0.5 kV. Particularly preferably, the surface potential is -0.1 kV to +0.1 kV. This surface potential can be adjusted by increasing or decreasing the type and amount of antistatic agent contained in the release agent layer.
[0143] Because the surface protective film 10 incorporates both fluorinated and siloxane surfactants in the adhesive layer 2, even small amounts of these surfactants can reduce the peeling static voltage during the removal of the surface protective film. Therefore, it can also be used for optical films treated with AR, LR, or AGLR. For example, it can also be used for optical films employing acrylic films, PET films, etc., which have low hygroscopicity and are easily charged. Therefore, the surface protective film 10 has a wide range of applications for adhered materials.
[0144] By reducing the amount of surfactant added, it is less likely to contaminate the adherends, thus simultaneously satisfying the opposite characteristics of adhering to the adhering and reducing peel electrostatic voltage. Therefore, with respect to the surface protective film 10, there is very little contamination of the adherends, and the peel electrostatic voltage when peeling the surface protective film 10 from the adherends can be suppressed to a low level.
[0145] Figure 2 This is a cross-sectional view showing the state where the release film 5 has been peeled off from the surface protective film 10. For example... Figure 2 As shown, the surface protective film 10 with the release film 5 peeled off is the film body 11. The film body 11 is composed of a substrate film 1 and an adhesive layer 2.
[0146] Figure 3 This is a cross-sectional view illustrating an embodiment of the optical component of the present invention.
[0147] like Figure 3 As shown, the release film 5 is peeled off from the surface protective film 10 to obtain the film body 11. The film body 11 is a surface protective film with the adhesive layer 2 exposed. The film body 11 is then attached to the optical component 8, which is the object to be adhered. The film body 11 is attached to the optical component 8 via the adhesive layer 2. The optical component 8 with the film body 11 attached is referred to as "optical component 20". The optical component 20 is an optical component with the surface protective film attached.
[0148] Examples of optical components that serve as the adhered material include polarizing plates, retardation plates, lens films, polarizing plates that also function as retardation plates, and polarizing plates that also function as lens films. Such optical components are used as constituent parts of liquid crystal display devices such as liquid crystal display panels, and optical systems for various measuring instruments. Other examples of optical components include anti-reflective films, hard coatings, and transparent conductive films for touch panels.
[0149] According to the optical component 20, when the surface protective film 10 (more specifically, the film body 11) is peeled off from the optical component 8 (e.g., an optical film) which is the adhered object, the peeling static voltage can be suppressed to a sufficiently low level. Therefore, damage to circuit components such as the driver IC, TFT elements, and gate line drive circuits can be prevented. As a result, production efficiency in the manufacturing process of liquid crystal display panels and the like can be improved, and the reliability of the production process can be maintained.
[0150]
Example
[0151] The present invention will be further described below through examples.
[0152] [Preparation of (meth)acrylate copolymer A]
[0153] 2-Ethylhexyl acrylate, methoxy polyethylene glycol (400) methacrylate, and 2-hydroxyethyl acrylate were copolymerized in a mass ratio of 80:17:3 to obtain an acrylate copolymer with a mass-average molecular weight of 550,000. 40 parts by mass of this acrylate copolymer were dissolved in 60 parts by mass of ethyl acetate to obtain (meth)acrylate copolymer A (40% solids in an ethyl acetate solution).
[0154] [Preparation of (meth)acrylate copolymer B]
[0155] 2-Ethylhexyl acrylate, butyl acrylate, methoxy polyethylene glycol (400) methacrylate, and 2-hydroxyethyl acrylate were copolymerized in a mass ratio of 70:20:7:3 to obtain an acrylate copolymer with a mass average molecular weight of 470,000. 40 parts by mass of this acrylate copolymer were dissolved in 60 parts by mass of ethyl acetate to obtain (meth)acrylate copolymer B (40% solids in an ethyl acetate solution).
[0156] [Preparation of peeling membrane a]
[0157] Five parts by mass of an addition-reaction type siloxane (manufactured by Dow Toray Industries, Inc., product name: SRX-345), 1.2 parts by mass of lithium bis(trifluoromethanesulfonyl)imide, 93.8 parts by mass of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.05 parts by mass of a platinum catalyst (manufactured by Dow Toray Industries, Inc., product name: SRX-212) were mixed and stirred to form a release agent layer of the release film a.
[0158] Using a Meller rod, the coating that forms the release agent layer is applied to the surface of a 25 μm thick polyethylene terephthalate film with a dry thickness of 0.2 μm, and then dried in a hot air circulating oven at 120°C for 1 minute to obtain release film a.
[0159] Addition-reaction type siloxanes are used as stripping agents. Lithium bis(trifluoromethanesulfonyl)imide (Li(CF3SO2)2N) is used as an antistatic agent.
[0160] [Preparation of release membrane b]
[0161] Using tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide (3M FC-4400, melting point 27.5°C) instead of lithium bis(trifluoromethanesulfonyl)imide as the antistatic agent in release film a, the same operation as that used to produce release film a was performed to obtain release film b.
[0162] Tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide is an antistatic agent.
[0163] (Example 1)
[0164] [Creation of a Surface Protective Film]
[0165] An adhesive composition was prepared by adding 0.04 parts by weight of Dow SilL-7002 (manufactured by Dow Toray Industries, Inc., a registered trademark) as a siloxane surfactant, 0.06 parts by weight of Surflon S-243 (manufactured by AGC Ching-mei Chemical Co., Ltd., a registered trademark) as a fluorinated surfactant, and 2 parts by weight of Coronate HX (manufactured by Tosoh Corporation, a registered trademark) as an isocyanate curing agent (crosslinking agent) to 100 parts by weight of (meth)acrylate copolymer A (40% solids content), and stirring and mixing.
[0166] Using an applicator, the prepared adhesive composition was applied to the surface of a 38 μm thick polyethylene terephthalate film (substrate film) with a dried adhesive layer thickness of 20 μm. Then, it was heated and dried in a hot air circulating oven at 100°C for 3 minutes to obtain an adhesive film. This adhesive film was constructed by forming an adhesive layer on one side of the polyethylene terephthalate film. Then, a release film a was attached to the surface of the adhesive layer with the release agent layer in contact with the adhesive layer. The resulting adhesive sheet was cured at 40°C for 3 days to obtain the surface protective film of Example 1 (siloxane surfactant / fluorinated surfactant mass ratio of 40 / 60).
[0167] (Example 2)
[0168] [Creation of a Surface Protective Film]
[0169] The amount of L-7002 added was 0.02 parts by mass, and the amount of Surflon S-243 added was 0.08 parts by mass. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Example 2 (the mass ratio of siloxane surfactant / fluorine surfactant was 20 / 80).
[0170] (Example 3)
[0171] [Creation of a Surface Protective Film]
[0172] The amount of L-7002 added was 0.09 parts by mass, and the amount of Surflon S-243 added was 0.01 parts by mass. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Example 3 (the mass ratio of siloxane surfactant to fluorine surfactant was 90 / 10).
[0173] (Example 4)
[0174] [Creation of a Surface Protective Film]
[0175] The amount of L-7002 added was 0.07 parts by mass, and the amount of Surflon S-243 added was 0.03 parts by mass. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Example 4 (the mass ratio of siloxane surfactant / fluorine surfactant was 70 / 30).
[0176] (Example 5)
[0177] [Creation of a Surface Protective Film]
[0178] Except for changing (meth)acrylate copolymer A to (meth)acrylate copolymer B, the same operation as in Example 1 was performed to obtain the surface protective film of Example 5 (mass ratio of siloxane surfactant / fluorine surfactant is 40 / 60).
[0179] (Example 6)
[0180] [Creation of a Surface Protective Film]
[0181] Using release film b instead of release film a, the same operation as in Example 1 was performed to obtain the surface protective film of Example 6 (mass ratio of siloxane surfactant / fluorine surfactant is 40 / 60).
[0182] (Example 7)
[0183] [Creation of a Surface Protective Film]
[0184] Using SF8410 (manufactured by Dow Toray Industries, Inc.) instead of L-7002, the same operation as in Example 1 was performed to obtain the surface protective film of Example 7 (mass ratio of siloxane surfactant / fluorine surfactant is 40 / 60).
[0185] (Example 8)
[0186] [Creation of a Surface Protective Film]
[0187] Using MEGAFAC F-470 (manufactured by D.E.S. Ltd., a registered trademark) instead of Surflon S-243, the same procedures as in Example 1 were performed to obtain the surface protective film of Example 8 (mass ratio of siloxane surfactant / fluorinated surfactant of 40 / 60).
[0188] (Example 9)
[0189] [Creation of a Surface Protective Film]
[0190] Using MEGAFAC F-477 (manufactured by D.E.S. Ltd., a registered trademark) instead of Surflon S-243, the same operation as in Example 1 was performed to obtain the surface protective film of Example 9 (mass ratio of siloxane surfactant / fluorine surfactant of 40 / 60).
[0191] (Comparative Example 1)
[0192] [Creation of a Surface Protective Film]
[0193] The amount of L-7002 added was 0.01 parts by mass, and the amount of Surflon S-243 added was 0.09 parts by mass. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Comparative Example 1 (the mass ratio of siloxane surfactant to fluorine surfactant was 10 / 90).
[0194] (Comparative Example 2)
[0195] [Creation of a Surface Protective Film]
[0196] The amount of L-7002 added was 0.1 parts by mass, and no Surflon S-243 was added. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Comparative Example 2 (mass ratio of siloxane surfactant / fluorine surfactant was 100 / 0).
[0197] (Comparative Example 3)
[0198] [Creation of a Surface Protective Film]
[0199] The amount of L-7002 added was 0.3 parts by mass. Otherwise, the same operation as in Comparative Example 2 was performed to obtain the surface protective film of Comparative Example 3 (the mass ratio of siloxane surfactant to fluorine surfactant was 100 / 0).
[0200] (Comparative Example 4)
[0201] [Creation of a Surface Protective Film]
[0202] Without using L-7002, the amount of Surflon S-243 added was set to 0.1 parts by mass. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Comparative Example 4 (mass ratio of siloxane surfactant / fluorine surfactant was 0 / 100).
[0203] (Comparative Example 5)
[0204] [Creation of a Surface Protective Film]
[0205] Except that the amount of Surflon S-243 added was set to 0.3 parts by mass, the same operation as in Comparative Example 4 was performed to obtain the surface protective film of Comparative Example 5 (the mass ratio of siloxane surfactant to fluorine surfactant was 0 / 100).
[0206] (Comparative Example 6)
[0207] [Creation of a Surface Protective Film]
[0208] Instead of release film a, a 25 μm thick release film (Mitsubishi Chemical Corporation, MRF-25) containing a general siloxane-based release agent without antistatic agent in the release agent layer was used. Otherwise, the same operation as in Example 1 was performed to obtain the surface protective film of Comparative Example 6 (without antistatic agent, and a mass ratio of siloxane-based surfactant to fluorinated surfactant of 40 / 60).
[0209] The following describes the methods and results of the evaluation experiment.
[0210] <Method for measuring the peel force of the release film>
[0211] The protective film was cut into pieces 50 mm wide and 150 mm long. The strength of the film when it was peeled off at a peeling speed of 0.3 m / min along a 180° direction was measured using a tensile testing machine. This strength was taken as the peeling force of the film (N / 50 mm).
[0212] <Method for measuring the low-speed adhesion strength of surface protective films>
[0213] An acrylic film (sometimes also called PMMA film) was used as a protective film for the polarizer. A low-reflection polarizing plate (LR polarizing plate) with a low-reflection treatment was laminated to the surface of a glass plate using a laminator. Then, a protective film cut to 25 mm wide was laminated to the surface of the polarizing plate and stored for one day at 23°C and 50% RH. The strength of the protective film when peeled at a peel speed of 0.3 m / min along a 180° direction was then measured using a tensile testing machine, and this strength was taken as the low-speed adhesive force (N / 25 mm).
[0214] <Method for measuring the high-speed adhesion of surface protective films>
[0215] PMMA film was used as a protective film for the polarizer. A low-reflection polarizing plate (LR polarizing plate) with a surface treated for low reflection was laminated to the surface of a glass plate using a laminating machine. Then, a protective film cut to 25 mm wide was laminated to the surface of the polarizing plate and stored for 1 day at 23°C and 50% RH. The strength of the protective film when peeled at a peeling speed of 30 m / min was then measured using a high-speed peel tester (Tester Industrial Manufacturing), and this strength was taken as the high-speed adhesive force (N / 25 mm).
[0216] <Method for measuring the peel electrostatic voltage of surface protective film>
[0217] PMMA film was used as a protective film for the polarizer. A low-reflection polarizing plate (LR polarizing plate) with a surface treated for low reflection was laminated to the surface of a glass plate using a laminating machine. Then, a surface protective film cut to a width of 25 mm was laminated to the surface of the polarizing plate and stored for 1 day at a test environment of 23°C and 50% RH. Then, while peeling the surface protective film at a peeling speed of 30 m / min using a high-speed peel tester (Tester Industrial Co., Ltd.), the surface potential of the polarizing plate surface was measured every 10 ms using a surface potentiometer (Keyence Corporation). The maximum absolute value of the surface potential at this time was taken as the peel static voltage (kV).
[0218] <Methods for confirming the surface contamination of surface protective films>
[0219] PMMA film was used as a protective film for the polarizer. A low-reflection polarizing plate (LR polarizing plate) with a surface treated for low reflection was laminated to the surface of a glass plate using a laminating machine. Then, a surface protective film cut to 25 mm wide was laminated to the surface of the polarizing plate, and the plate was stored at 23°C and 50% RH for 3 days and 30 days. Afterward, the surface protective film was peeled off, and the surface contamination of the polarizing plate was visually inspected. As a criterion for judging surface contamination, no contamination transfer was defined as (○: good), and contamination transfer was confirmed as (×: bad).
[0220] For the surface protective films obtained in Examples 1-9 and Comparative Examples 1-6, the measurement results are shown in Tables 1-4. "Siloxane / Fluorine mass ratio" refers to the addition ratio of siloxane surfactants to fluorine surfactants (mass ratio of siloxane surfactants to fluorine surfactants).
[0221] (Table 1)
[0222]
[0223] (Table 2)
[0224]
[0225] (Table 3)
[0226]
[0227] (Table 4)
[0228]
[0229] (Table 5)
[0230]
[0231] The following information can be obtained from the measurement results shown in Tables 1 to 5.
[0232] The surface protective films of Examples 1-9 have suitable adhesive strength, do not contaminate the surface of the adhered object, and have low peeling static voltage when the surface protective film is peeled off from the adhered object.
[0233] On the other hand, for the surface protective film of Comparative Example 1, where the mass ratio of siloxane surfactant to fluorine surfactant was set to 10 / 90, the peeling electrostatic voltage when the surface protective film was peeled from the adhered object was higher. Furthermore, in Comparative Examples 2 and 3, where no fluorine surfactant was used, if the amount of siloxane surfactant added was low, the peeling electrostatic voltage when the surface protective film was peeled from the adhered object was higher. If the amount of siloxane surfactant added was increased, the peeling electrostatic voltage when the surface protective film was peeled from the adhered object decreased, but the surface contamination of the adhered object worsened.
[0234] In Comparative Example 4, which did not use any siloxane surfactants, the peeling electrostatic voltage when the protective film was peeled from the adhered object was high. In Comparative Example 5, which increased the amount of fluorinated surfactants, the peeling electrostatic voltage when the protective film was peeled from the adhered object did not become very low. Moreover, the surface contamination of the adhered object also worsened. In Comparative Example 6, where the release agent layer of the release film did not contain an antistatic agent, the peeling electrostatic voltage became extremely high.
[0235] When using an LR polarizing plate that tends to have a high peel electrostatic voltage and becomes easily observable for contamination, a surface protective film was also obtained by using a siloxane surfactant and a fluorinated surfactant at a predetermined ratio. This surface protective film has a low peel electrostatic voltage when peeled off and does not contaminate the adhered material.
[0236] Industrial availability
[0237] One aspect of the surface protective film of the present invention can be used, for example, in the production processes of optical films such as polarizers, retardation plates, and lens films, as well as various other optical components, to protect the surface of these components. Furthermore, the surface protective film of the present invention can reduce the amount of static electricity generated when peeling from the adhered object, and its anti-peel static electricity performance changes over time with minimal contamination of the adhered object, thereby improving the yield of the production process and possessing significant industrial application value.
Claims
1. A surface protective film, characterized in that, have: The substrate film is made of a transparent resin; An adhesive layer is formed on one side of the substrate film; and A release film is formed on the side of the adhesive layer opposite to the substrate film. The peeling membrane has the following characteristics: Resin film; as well as A release agent layer, which is laminated on one side of the adhesive layer of the resin film. The release agent layer contains a release agent and an antistatic agent with dimethylpolysiloxane as the main component. The adhesive layer is formed of an adhesive containing (meth)acrylate copolymer, siloxane surfactant, fluorinated surfactant and crosslinking agent. The crosslinking agent crosslinks the (meth)acrylate copolymer. The ratio of the siloxane surfactant to the fluorinated surfactant in the adhesive is 20 / 80 to 70 / 30 by mass, calculated based on solid components. The antistatic agent is an alkali metal salt or an ionic liquid. The solid content of the antistatic agent is 5 to 100 parts by weight relative to 100 parts by weight of the solid component of the stripping agent. The amount of the siloxane surfactant added is 0.005 to 0.5 parts by weight relative to 100 parts by weight of the (meth)acrylate copolymer. The amount of the fluorinated surfactant added is 0.005 to 0.5 parts by weight relative to 100 parts by weight of the (meth)acrylate copolymer.
2. The surface protective film according to claim 1, characterized in that, The (meth)acrylate copolymer is a copolymer comprising one or more of alkyl acrylates, acrylates with olefinic groups, and acrylates with hydroxyl groups.
3. The surface protective film according to claim 1 or 2, characterized in that, The surface protective film exhibits a low-speed adhesive force of less than 0.2 N / 25 mm at a peel speed of 0.3 m / min relative to the low-reflection polarizing plate, and a high-speed adhesive force of less than 0.8 N / 25 mm at a peel speed of 30 m / min. The static voltage during stripping is -0.7kV to +0.7kV.
4. An optical component, characterized in that, The surface protective film as described in claim 1 or 2 is adhered to it.
Citation Information
Patent Citations
Surface protecting film and optical component whereon it is stuck
JP2005131957A
Adhesive composition, adhesive sheet and surface-protective film
JP2005314476A
Pressure sensitive adhesive composition and pressure sensitive adhesive sheet
JP2005330464A
Adhesive composition, adhesive sheets and surface protection film
JP2006152235A
Surface protective film
JP2011063712A